THE IMPORTANCE OF LANGUAGE LEARNING FOR EARLY CHILDREN IN KASREMAN VILLAGE, KANDANGAN, KEDIRI - Agustina, Ria Kamilah; Nurul Laili, Elisa; Daristin, Pipit Ertika; Indrawan, Fani; Fajarina, Maskhurin; Zuhriyah, Mukminatus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Language is the ability to communicate with others, encompassing various forms such as verbal, written, gestures, numbers, drawings, and facial expressions. It allows people to express thoughts, feelings, and ideas using symbols. Effective communication requires language skills, which are essential for humans to connect with one another. Language is a key factor that distinguishes humans from animals, enabling individuals to understand themselves, others, and their surroundings. Through language, people can share their thoughts, preferences, and ideas. In Kasreman village, Kanangan subdistrict, Kediri district, many children cannot communicate well, which is due to a lack of interaction between parents and children. Based on this, it inspired the PKM team consisting of UNHASY lecturers and students to carry out PKM with the title